EVALUATION OF STORAGE TIME AT ROOM TEMPERATURE JUDGING FROM THE PHYSICOCHEMICAL AND MICROBIOLOGICAL PROPERTIES OF ETAWAH DAIRY12 GOAT MILK - F. S., Anggreini; Okarini, I. A.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika; Vol 7 No 1 (2019): Vol. 7 Isssues 1 (2019); January - April 2019, 2019)
The research aims to determine the physicochemical and microbiological properties of fresh goat milk in terms of protein content, consistency, boiling test and total microbes. The sample were obtained from fresh PE goat milk of UD. Bali Sariwangi located at Puncak Sari Village, Busungbiu District, Buleleng Regency, Bali. This research was carried out at the Dairy Farm Laboratory, and the Animal Product Technology Laboratory, the Faculty of Animal Science as well as the Food Analysis Laboratory the Faculty of Agricultural Technology, Udayana University Jl. PB Sudirman, Denpasar. This research took from June to July 2018. The experimental design used was a Completely Randomized Design (CRD) consisted of 3 treatments and 4 replicated. The treatments were a control (L0), 4-hour storage time (L4) and 6-hour storage time (L6). The variables observed were protein content, consistency, boiling test and total microbes. The results showed that protein levels in the L4 and L6 treatments were low by 0.91% and 15.25% respectively, but statistically the protein content in the L4 treatment was not different from the control (P> 0.05). The results of the consistency in the L4 and L6 treatments were significantly (P <0.05) lower at 28.75% and 52.43% respectively. The boiling test results show positive results at 6 hours storage. The total microbial of L4 and L6 treatments were significantly increase of 57.48% and 42.53% respectively. From the results of this study it can be concluded that the storage time at room temperature affects the physicochemical properties (protein content, consistency, boiling test) and microbiology (total microbes). Long time to keep goat milk at room temperature is 4 hours. Keywords: storage duration, goat milk, protein, viscosity, boiling test, total microbes.